Magnetic exchange couplings with range-separated hybrid density functionals - Peralta, Juan E. (2010)
We investigate the effect of Hartree-Fock range-separation on the calculation of magnetic exchange couplings in a set of nine bimetallic transition-metal complexes containing 3d elements (V, Cr, Mn, and Cu). To this end, we have compared magnetic exchange couplings calculated as self-consistent energy differences using two global hybrid functionals, B3LYP (Becke 3-parameter exchange and Lee-Yang-Parr correlation) and PBEh (hybrid Perdew-Burke- Ernzerhof) with the short-range separated HSE (Heyd-Scuseria-Ernzerhof) and the long-range corrected LC-ωPBE. Our results show that, although there is no clear superiority of any of these functionals when compared with experimental data, the LC-ωPBE provides a better description of the magnetization on the metallic centers, yielding self-consistent solutions that mimic more closely a Heisenberg-like behavior. © 2010 American Chemical Society.